Description Of Pregnant Women's Knowledge About Anemia - Windari, Fitri; Rosmawati, Dwi; Anggaraini, Heni; Ningsih, Tri Riwayati (Journal of Applied Health Management and Technology, 2023)
Background :: Anemia is a health problem that affects people worldwide and affects both developed and developing countries. Anemia occurs during every human life cycle, with one in four suffering from anemia. Most people with anemia are pregnant women. Anemia is an indirect cause of death for pregnant women. According to the World Health Organization (WHO), defines anemia during pregnancy as a hemoglobin level of less than 11 g or less than 33% at any time during pregnancy. The hemoglobin level during pregnancy is less than 11 g and is in early pregnancyObjective: Explain the characteristics of pregnant women's knowledge about anemia based on age, education level, and mother's occupationMethods: Quantitative descriptive research with a study with a total of 56 respondents in the Working Area of the Karang Anyar Health Center, South Lampung. Data collection used a questionnaire sheet, data testing was carried out using Chi Square.Research result: the characteristics of the respondents which include age, education level, and mother's occupation, most of the respondents are aged 20-35 years, with a high school education level, the second article has elementary school education, and the respondent's occupation is that most of the respondents do not work. An overview of pregnant women's knowledge about anemia was obtained from the majority in the sufficient category. Knowledge can be influenced by the support factor from the family. Other factors that can help pregnant women's knowledge about anemia with education and information from health workers must be further improved so that the quality of knowledge of pregnant women will be even betterConclusion: Knowledge of pregnant women about anemia can be influenced by factors from family support and health workers, education of pregnant women and motivation for health education so that the quality of knowledge of pregnant women is getting better.